What Would Sakharov Say? The Americanization of Andrei Sakharov - Rubinson, Paul (Journal of Russian American Studies, 2024)
During the 1970s and 1980s, American scientists rallied to defend Andrei Sakharov, a Soviet physicist punished for his advocacy of human rights. In the United States, Americans of all political persuasions admired Sakharov’s courage, though they expressed it in different ways. To some, his life inspired a pursuit of social change, while others saw his plight as confirmation of the evils of Soviet communism. More than anything, though, Sakharov’s moral authority was a highly sought and politically useful prize. Scholars assessing the campaign to save Sakharov have noted divisions within the movement over effort and tactics, but as this paper argues, the movement was, during Sakharov’s life and after, a political struggle among various Americans groups to claim his mantle as their own.